Rancang Bangun Web Service API Aplikasi Apotek Online Menggunakan Metode REST - Tapa Mahendra, I Putu Fajar; Santiyasa, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
The development of information technology is very rapid, making information technology an important part of our lives that cannot be separated. Due to the effectiveness and efficiency of information technology, it is also used in the business realm to assist in developing existing businesses, one of which is e-business. To support transaction processing in e-business, we need a web service that can be accessed anywhere. In the application of web services, researchers can use the REST architecture. In the test, the Blackbox method is used. Blackbox method is a software test that is carried out by entering an input into the software and then checking whether the output produced by the software is in accordance with the expected results. from the test results, the results are 100% successful